توظيف الإشهار الضمني في السينما العربية - مزوار,إيمان; مناعي,تركية (University of Eloued جامعة الوادي, 2024)
هدفت هذه الدراسة للتعرف على كيفية توظيف الإشهار الضمني في السينما العربية , حيث تعد السينما وسيلة جد فعالة من ناحية تأثيرها الثقافي , وبذلك تسعى الشركات والعلامات التجارية أن تستخدم الأفلام لترويج السلع والخدمات .هذه الممارسة الإشهارية في الأفلام العربية التي تكون بطريقة غير مباشرة في عرضها بحيث تأثر على الجمهور وتكوِن لهم أنماط استهلاكية . و ترتبط القيم ,الإيديولوجية , المعتقدات والتقاليد ارتباطا وثيقا بالإشهار في الأفلام ,فالمنتوجات والخدمات الموظفة ليست مجرد أشياء اعتباطية وإنما تبنى على أسسسميولوجية (أي رسائل ضمنية ) . وعليه تناولنا في هذه الدراسة السيميولوجيةالإشهار الضمني للسينما العربية والذي يتعلق أساسا بتحديد الجوانب الرمزية لتوظيف المنتوجات والعلامات في الأفلام العربية . فالهدف من هذه الدراسة السيميولوجية هو استنطاق الدلالات الكامنة في الأفلام , بالاعتماد على المنهج السيميولوجي في اختيار العينة القصدية ووصفها وتحليلها ودراستها , وللإجابة على إشكالية الدراسة , تم الاعتماد على مجموعة من أدوات جمع البيانات المتمثلة في : الملاحظة , أدوات المنهج السيميولوجي. من خلال تحليل سيميولوجي لعينة من مشاهد من فليمي أبو شنب ولف ودوران بالاعتماد على مقاربة السيميولوجي الفرنسي رولان بارث كأداة بحثية ,ولقد توصلنا إلى جملة من نتائج أهمها : أن معظم الدلالات الموظفة في صورة الإشهارية المقدمة في فليمين أبو شنب ولف ودوران كان لهما دور كبير في توجيه الأذهان نحو تقليد الأعمى بحيث تضمنا دلالات تحيل الى بعض الجوانب السلبية, مثل خروج الرجل من دائرة الأقارب وأصبح يكون علاقات صداقة خارج إطار العائلة ,وتحرر المرأة في طريقة لبسها . تعمل الرسالة الإشهارية في أفلام العربية على نشر وغرس الثقافة الاستهلاكية ,تبين ذلك من خلال تحليلنا حسب عينة الدراسة إنتاج نموذج حياة فريدة وموحدة تستهلك فيها نفس الخدمات والمنتوجات في كل مكان بالتالي خلق ثقافة استهلاكية موحدة. ركزت بنية الرسائل الإشهارية في أفلام العربية على ربط العلامات والمنتوجات بالموضوعات الإنسانية (الرفاهية والراحة ) كما وجدنا أن مضامين الرسالة الإشهارية يستند على حوافز النفسية لتمرير الدلالات . تفوقت السينما العربية بفضل التكنولوجيا وإبداعاتها في إنتاج الأفلام وذلك من خلال طرحها للأفكار ورسائل الأيديولوجية عبر رسائل إشهارية داعمة بذلك تحرر المرأة ودخولها عالم العمل ومنافسة الرجل في المهن الشاقة وإتباع الرجل للنمط الغربي . Résumé :انجليزية This study aimed to identify how to employ implicit advertising in the Arabic cinema, where cinema is a Very effective means in terms of their cultural impact, so companies and brands seek to use films to promote Goods and services, this advertising practice in the Arabic films is presented indirectly in their presentation. So that they affect the public and have consumption patterns. Values, ideology, beliefs and traditions are closely linked to publicity in films. The products and services employees are not just arbitrary objects, but are built on semiological foundations (i.e. implicit messages). Accordingly, in this semiological study, we dealt with the implicit publicity of the Arabic cinema, which is mainly related to the identification of Symbolic aspects of employing products and marks in Arabic films. The aim of this semiological study is to interrogate the connotations inherent in films, depending on the methodology of Semiology in the selection, description, analysis and study of the sample, and to answer the problem of the study, a set of data collection tools were relied on: observation, semiological approach tools. Through a semiological analysis of a sample of scenes from Abu Shanab’s film Wolf and Turn, relying on the approach of the French semiologist Roland Barthes as a research tool, we have reached a number of results, the most important of which are: Most of the connotations used in the form of advertising presented in Film Abu Shanab and Wolf and Duran played a major role in directing minds towards imitating the blind, as they included connotations that referred to some negative aspects, such as the man leaving the circle of relatives and starting to form friendship relationships outside the framework of the family, and the emancipation of women. In the way she dresses. The advertising message in Arabic films works to spread and instill consumer culture. This was shown through our analysis, according to the study sample, to produce a unique and unified model of life in which the same services and products are consumed everywhere, thus creating a unified consumer culture. The structure of advertising messages in Arabic films focused on linking brands and products to human themes (luxury and comfort). We also found that the contents of the advertising message are based on psychological incentives to convey connotations. Arab cinema excelled thanks to technology and its creativity in film production, by presenting ideas and ideological messages through advertising messages, thus supporting the liberation of women and their entry into the world of work, competing with men in difficult professions, and making men follow the Western style.
دراسة تحليلية سميولوجية لفيلمي أبو شنب ولف ودوران
Keywords: الفيلم السينمائي; السينما العربية; الإشهار الضمني; الرسالة الاشهارية; Implicit publicity; Arabic cinema; Arabic film. advertising message; Advertising.